Analysis of Independent Learning Policies Episode 17 (Revitalization Language Area) - Ferika Aulia Marwadi (Proceeding International Conference on Religion, Science and Education, 2023)
Regional language is the first language a person acquires in society and family. With time development _ this create regional languages Becomes forgotten inside _ scope family. to revitalize this regional language it is necessary to realize concrete things so that the successors nation permanent own teak self area with the regional language they master. Look from these problems, the authors provide suggestions for developing regional language teaching materials as local content. this _ proposed because learning be one _ expected effort _ able to convey understanding to students in give appropriate language knowledge with purpose regional language revitalization. So in trouble the the government is expected to be able to provide appropriate and structured solutions, researchers found policies government about regional language revitalization which is expected to be an important step in the efforts made to revitalize regional languages, so that the goal of regional language revitalization can be achieved. done well to maintain and maintain identity and ideology society and ethnicity.